Research on residual service life of automatic locking valve of turbine K-200-130 - Chernousenko, Olga; Rindyuk, Dmitro; Peshko, Vitaliy (Eastern-European Journal of Enterprise Technologies, 2017)
Calculations of non-stationary thermal and stress-strain state of the casing of ALV of HPC under combined effect of temperature gradient and operational internal steam pressure were performed. Temperature gradients and pressures were assigned by variables in time under starting operation modes in accordance with actual schedules of starts, determined by the power plant. In geometric modeling, valve’s lid was taken into consideration. Taking into account the lid did not have a significant impact on durability of ALV of HPC. The estimation of damage and residual service life of casings of ALV of HPC of the steam turbine K-200-130-3 showed that the total damage of metal of the casings of ALV of HPC is 84 %. The estimated residual service life of metal of the casing of ALV of HPC of the turbine K-200-130 will increase up to 164,383 hours when refining safety factors. This will make it possible to extend operation of casings of ALV of HPC by 50 thousand hours at the number of starts, equal to half the park number, that is 400 starts. To increase reliability of the elements of the turbine, to decrease thermal loads and improve the quality of operation, it is necessary to optimize the number of starts from cold state in direction of a decrease. It is also necessary to refine safety factor of metal of casings of ALV of HPC by deformations nε, the number of cycles nN, limits of fluidity nf and safety by nominal stresses nns. To do this, it is necessary to conduct studies on the impact of ageing on changes in physical-mechanical properties of structural alloy steels under operational and elevated temperatures. Results of the conducted research can be used to extend service life of locking and protective valves of steam turbines of large capacity in the energy sector.